Andres Bonifacio: proletarian hero of the Philippines and Indonesia. Issue 3 (3rd July 2017) - Guillermo, Ramon
ABSTRACT: The concluding chapter of Tan Malaka's (1897–1949) large philosophical work entitled Madilog: Materialisme, Dialektika, Logika contains interesting reflections on the extent and scope of the future liberated and sovereign Indonesian nation and on the concept of "Indonesian" heroism and nationality. However, most striking of all is the uppermost position he allots in his schema for Philippine national heroes such as Dr. Jose Rizal, the patriot and writer, and Andres Bonifacio, the leader and founder of the Katipunan, the most successful Philippine revolutionary anti-colonial organization.